1984
DOI: 10.1002/1097-0142(19841215)54:12<2927::aid-cncr2820541219>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Antigens and circulating immune complexes related to the primate retroviral glycoprotein SiSVgp70: Indicators of early mortality in human acute leukemias and chronic myelogenous leukemias in blast crisis

Abstract: Human sera contain antigens and also circulating immune complexes that are related to the primate retroviral envelope glycoprotein gp70 of simian sarcoma/simian sarcoma associated virus (SiSV) and of gibbon ape leukemia virus (GaLV). SiSVgp70 related antigens (AG) and immune complexes (IC) are detected both in leukemic and in nonleukemic sera.23 In a further analysis of these data, the prognostic significance of SiSVgp70 related AG and IC indicates an unfavorable clinical course and a shorter survival time in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The evidence for the occurrence of HERV antigens in human blood is well documented. We discussed above the find-ings of Jacquemin et al (80), Hehlmann and his coworkers (66)(67)(68), and Derks et al (42). In some instances, the molecular nature of the antigens was determined.…”
Section: Discussionmentioning
confidence: 92%
“…The evidence for the occurrence of HERV antigens in human blood is well documented. We discussed above the find-ings of Jacquemin et al (80), Hehlmann and his coworkers (66)(67)(68), and Derks et al (42). In some instances, the molecular nature of the antigens was determined.…”
Section: Discussionmentioning
confidence: 92%
“…The evidence for the occurrence of HERV antigens in human blood is well documented. We discussed above the find-ings of Jacquemin et al (80), Hehlmann and his coworkers (66)(67)(68), and Derks et al (42). In some instances, the molecular nature of the antigens was determined.…”
Section: Vol 9 1996 Human Endogenous Retroviruses 93mentioning
confidence: 92%
“…Again, no formal proof linking such activities to HERV expression was obtained. The very interesting study by Hehlmann and his associates (67) reported that sera from leukemic patients (mostly some form of myelomonocytic leukemia) contained antigens and immune complexes related to gp70 of SSV and gibbon ape leukemia virus. Some nonleukemic sera also contained such complexes.…”
Section: Hervs and Autoimmune Diseasementioning
confidence: 99%
See 1 more Smart Citation